PENGARUH EFISIENSI BIAYA TERHADAP TINGKAT KESEHATAN KOPERASI SIMPAN PINJAM (KSP) DAN UNIT SIMPAN PINJAM (USP) (STUDI PADA KOPERASI DI SURAKARTA TAHUN 2015) - Nurul Ulfah Hidayati; Sri Suranta (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2016)
This paper aims to determine the influence of cost efficiency by six proxies on each KSP and USP Cooperative which has been assessed by Dinas Koperasi and UMKM Surakarta in 2015 on the level of health of the cooperative based on the results of the cooperative health assessment. In total, KSP and USP Cooperative samples in this paper were 25 cooperative that have been assessed an implement RAT in 2016. This research method using a model of quantitative research. The data analysis technical use analysis of the ratio consisting of 6 ratios (BOAPB, BUSK, EP, RA, RMS, and KOP) is calculated with guidelines health assessment to generate score ratings healthy assessment cooperative on each ratios and multiple linear regression analysis with independent variable cost efficiency and the dependent variable levels of health cooperative. Based on the research it was found that the level of efficiency by 6 proxies KSP and USP Cooperative on average have sufficient predicates efficient. However, the results also found 2 of 6 proxies affect cost efficiency and 4 proxies do not affect the level of health cooperatives. Then, the results of the paper concluded that the cost efficiency 4 proxies has no the influence because the paper sample indicated divergence conducted by KSP and USP Cooperative, these statements are based on the data obtained and the analysis of the health assessment score of each ratio. Therefore, 4 proxies is not significant influence partially.